Electrochemical discharge of Li-ion batteries - A methodology to evaluate the potential of discharge electrolytes without corrosion. (25th November 2022) - Rouhi, Hassan; Serna-Guerrero, Rodrigo; Santasalo-Aarnio, Annukka
Abstract: The demand for Lithium-ion batteries (LIB) is expected to increase exponentially due to the electrification of society. Thus, recycling LIBs will be essential to support this activity and ensure the availability of the limited raw material. End-of-life batteries entering the recycling process may still contain energy, representing a safety risk for processing. The energy can be drained in an electrochemical discharge before mechanical crushing, and it has been proposed that an aqueous NaCl solution would be suitable media. The field has lacked an accurate tool to evaluate the suitability of an electrolyte for LIB discharge. In this work, we intoduce two methods: external and internal electrochemical discharge. We also validate the methodology selection with ammonia-based electrolytes and provide a corrosion-free evaluation of the role of NaCl as an electrochemical discharge medium. The new methodology results confirmed that the batteries could be discharged to low voltage levels in NaCl electrolytes. Still, this electrolyte is highly corrosive, preventing the recovery of active materials in high purity. Thus, with the new methodology, finding alternative salt solutions that provide an efficient and non-corrosive discharge environment will be fast. Highlights: Due to increasing demand on LIBs, an efficient and safe recycling process is vital. Batteries at their end-of-life might be hazardous due to their remnant energy. External electrochemical discharge can be used to eliminate the effect of corrosion. Some measurement devices may involve in discharging the batteries during experiments.